A scoping review on hyposalivation associated with systemic conditions: the role of physical stimulation in the treatment approaches - Jéssica Luiza de Mendonça Albuquerque Melo; Camila Pinho e Souza Coelho; Fernanda de Paula e Silva Nunes; Debora Heller; Daniela Corrêa Grisi; Maria do Carmo Machado Guimarães; Naile Dame-Teixeira (BMC, 2023)
Abstract Background Several systemic conditions can result in distinct degrees of salivary gland damage and consequent hypofunction. The development of successful management schemes is highly challenging due to the complexity of saliva. This study aimed to systematically map the literature on the physical stimulation of salivary glands for hyposalivation management and the response of individuals according to different systemic conditions causing salivary impairment. Methods A systematic search in the literature was performed. Two reviewers independently selected clinical trials, randomized or not, that used physical stimulation to treat hyposalivation caused by systemic conditions. Studies evaluating healthy subjects without hyposalivation were included as controls. Single-arm clinical studies or case series were also included for protocol mapping (PRISMA extension for scoping reviews). Results Out of 24 included studies, 10 evaluated healthy subjects, from which 9 tested transcutaneous electrical nerve stimulation (TENS) and 1 tested acupuncture and electroacupuncture. Fourteen studies evaluated individuals with hyposalivation: 6 applied TENS, 6 applied low-level laser therapy (LLLT), and 2 applied acupuncture, carried out in post-chemotherapy, medication use, postmenopausal women, hemodialysis patients, smokers, diabetics, Sjögren's syndrome (SS). All showed increased salivation after treatment, except for two LLLT studies in individuals with SS. Conclusions Among the different patient groups, individuals with Sjögren's syndrome (SS) exhibited the poorest responses, while those with medication-induced hyposalivation demonstrated the most favorable treatment outcomes, independently of the management strategy for saliva stimulation. It means that physical stimulation of salivary glands holds promise as an alternative for managing hyposalivation in cases of reversible gland damage. However, to make informed decisions in current practice, it is necessary to conduct new well-designed randomized clinical trials with appropriate methodologies.